Analysis of DAT1 (SLC6A3) RS27072 gene polymorphism, parenting style, and internet addiction tendency in adolescents: A cross-sectional study - Irawan, Andi Ummulkhair Pawallangi; Renaldi, Rinvil; Limoa, Erlyn; Idris, Irfan; Wahid, Isra; Lisal, Sonny Teddy; Syamsuddin, Saidah (Edelweiss Applied Science and Technology, 2025)
To determine the relationship between DAT1 (SLC6A3) rs27072 gene polymorphism and parenting style in adolescents with a tendency toward internet addiction. Cross-sectional study of 443 adolescents aged 10-19 years. The study identified adolescents with a tendency toward internet addiction using the Internet Addiction Diagnostic Questionnaire (KDAI), with 84 meeting the inclusion criteria and 311 without a tendency. Parenting style was assessed using the Child Parenting Questionnaire (KPAA). The DAT1 (SLC6A3) rs27072 gene polymorphism was examined in 84 adolescents with a tendency toward internet addiction and 39 without, using PCR-RFLP and restriction enzyme methods. Statistical analysis employed Fisher’s exact test and chi-square test to evaluate relationships between variables, with a significance level of p < 0.05, and binary logistic regression to predict the probability of an event based on predictor variables. The results indicated that the DAT1 (SLC6A3) rs27072 gene polymorphism is significantly associated with internet addiction tendencies in adolescents, with most exhibiting GG bands, while adolescents without such tendencies mostly display TT and TG bands. Parenting styles are also significantly associated, with adolescents exhibiting internet addiction tending to have permissive parenting, whereas non-addicted adolescents mostly have democratic parenting styles. The combination of DAT1 (SLC6A3) rs27072 gene polymorphism and parenting style is significantly associated with internet addiction tendencies. Specifically, the G allele of the DAT1 gene and an exposure (permissive) parenting style are linked to a higher likelihood of internet addiction in adolescents.